Comparison of Various Approaches to Tagging for the Inflectional Slovak Language - Benko, Lubomir; Munkova, Dasa; Pappova, Maria; Munk, Michal (PEERJ INC, 2024)
Morphological tagging provides essential insights into grammar, structure, and the mutual relationships of words within the sentence. Tagging text in a highly inflectional language presents a challenging task due to word ambiguity. This research aims to compare six different automatic taggers for the inflectional Slovak language, seeking for the most accurate tagger for literary and non-literary texts. Our results indicate that it is useful to differentiate texts into literary and non-literary and subsequently, based on the text style to deploy a tagger. For literary texts, UDPipe2 outperformed others in seven out of nine examined tagset positions. Conversely, for non-literary texts, the RNNTagger exhibited the highest performance in eight out of nine examined tagset positions. The RNNTagger is recommended for both types of the text, the best captures the inflection of the Slovak language, but UDPipe2 demonstrates a higher accuracy for literary texts. Despite dataset size limitations, this study emphasizes the suitability of various taggers for the inflectional languages like Slovak.
Srovnání různých přístupů k tagování pro flektivní slovenský jazyk
Keywords: Part-of-speech tagging; Low-resource language; Slovak language; Morhological annotation; Automatic taggers; PoS tagování; Nízkozdrojový jazyk; Slovenský jazyk; Morfologická anotace; Automatické tagování